Analysis of Entropy Production of Immiscible Micropolar and Newtonian Fluids Flow through a Channel: Effect of Thermal Radiation and Magnetic Field - Pramod Kumar Yadav; Kumar, Ankit; Filippov, A. N. (Colloid journal of the Russian Academy of Sciences, 2023)
This paper aims to analyze the thermal characteristics, entropy production, flow velocity and Bejan number profile for immiscible nature of micropolar and Newtonian viscous fluid within a channel. Here, the authors emphasize the influence of thermal radiation and oriented magnetic field on the thermal profile and entropy generation of two different types of non-miscible and incompressible micropolar and Newtonian fluids in a channel. The viscous dissipation and thermal radiation effect are also considered in the thermal energy equation. In this work, the entropy production is analyzed within a channel due to oriented magnetic field and thermal radiation. A constant pressure gradient acts on the entry zone of flow domain and static walls of the channel are isothermal. In this problem, we tried to simulate thermal radiation in energy equation by adopting the Rosseland’s diffusion approximation. According to geometrical configuration of the problem, the conditions of no-slip at the walls of the channel and continuity of thermal exchange, microrotation, shear stress, flow velocity and heat flux at the interface of immiscible fluids are used. The governing equations for the flow of immiscible fluids are solved by reliable technique and exact solution for thermal characteristics and flow field are evaluated. The mathematical results of thermal profile and flow characteristics are used to obtain the Bejan number profile as well as the entropy production number profile. The influence of various thermo-physical governing parameters such as radiation parameter, Reynolds number, inclination angle parameter, viscous dissipation parameter, micropolarity parameter and Hartmann number, which describe the physical significance of the present model, on the flow and thermal characteristics of the model are discussed graphically. The newly obtained results of this study are verified with previous published results.